The diet of Eurasian Tree Sparrow Passer montanus nestlings in relation to agri-environment scheme habitats. Issue 2 (2nd April 2016) - McHugh, Niamh M.; Prior, Matt; Leather, Simon R.; Holland, John M.
ABSTRACT: It has been suggested by some authors that the UK agri-environment 'wild bird seed' option negatively impacts Tree Sparrow populations in the UK. Here we provide evidence for a change in nestling diet with increasing wild bird seed coverage and propose a possible mechanism for its negative impact on population trends.